Against transmission : media philosophy and the engineering of time - Barker, Timothy (Bloomsbury Academic, 2018)
Against Transmission introduces the technical history and phenomenology of media, a field of study that explains the characteristics of contemporary life by looking to the technical properties of machines. By studying the engineering of signal processing, the book interrogates how the understanding of media-as-machine exposes us to a particular phenomenological relationship to the world, asking: what can the hardware of machines that segment information into very small elements tell us about experiences of time, memory and history?This book offers both a detailed and radical investigation of the technical architecture of media such as television, computers, cameras, and cinematography. It achieves this through in-depth archive research into the history of the development of media technology, combined with innovative readings of key concepts from philosophers of media such as Harold A. Innis, Marshall McLuhan, Friedrich Kittler, Siegfried Zielinski and Wolfgang Ernst. Teaming philosophical inquiry with thorough technical and historical analysis, in a broad range of international case studies, from early experimental cinema and television to contemporary media art and innovative hardware developments, Barker shows how the technical discoveries made in these contexts have engineered the experiences of time in contemporary media culture.